Energy, sustainability, and the environment technology, incentives, behavior - Sioshansi, Fereidoon P. (Butterworth-Heinemann, 2011)
"The complexity of carbon reduction and economic sustainability is significantly complicated by competing aspects of socioeconomic practices as well as legislative, regulatory, and scientific requirements and protocols. An easy to read and understand guide, Sioshansi, along with an international group of contributors, moves through the maze of carbon reduction methods and technologies, providing steps and insights to meet carbon reduction requirements and maintaining the health and welfare of the firm"--Provided by publisher.
Keywords: Renewable energy sources.; Energy conservation -- Social aspects.; elektronické knihy; electronic books